2018
DOI: 10.3390/nu10030375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on Glycemic Control in Type 2 Diabetes Patients: A Systematic Review and Meta-Analysis

Abstract: Observational studies have indicated an inverse association between vitamin D levels and the risk of diabetes, yet evidence from population interventions remains inconsistent. PubMed, EMBASE, Cochrane Library and ClinicalTrials.gov were searched up to September 2017. Data from studies regarding serum 25(OH)D, fasting blood glucose (FBG), hemoglobin A1c (HbA1c), fasting insulin and homeostasis model assessment of insulin resistance (HOMA-IR) were pooled. Twenty studies (n = 2703) were included in the meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 39 publications
2
98
0
22
Order By: Relevance
“…In 2017, a systematic review and meta-analysis reported that the dose of vitamin D supplementation ≥ 1000 IU/day had a reducing effect on FBG levels [37]. Recently, a systematic review and meta-analysis indicated that daily doses of vitamin D ≥ 2000 IU/day had a positive impact on glycemic control [43]. In relation to calcium, it is difficult to determine the insufficiency of calcium status by biochemical methods, but suboptimal intake of calcium has been reported in different populations [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, a systematic review and meta-analysis reported that the dose of vitamin D supplementation ≥ 1000 IU/day had a reducing effect on FBG levels [37]. Recently, a systematic review and meta-analysis indicated that daily doses of vitamin D ≥ 2000 IU/day had a positive impact on glycemic control [43]. In relation to calcium, it is difficult to determine the insufficiency of calcium status by biochemical methods, but suboptimal intake of calcium has been reported in different populations [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a systematic review reported that short-term supplementation of vitamin D supplementation had a beneficial effect on glycemic control [16]. Furthermore, a recent systematic review and meta-analysis indicated that high-dose and short-term supplementation of vitamin D alone had beneficial effects on insulin resistance and FBG [43]. However, in 2017, a systematic review and meta-analysis reported that neither short-term and nor long-term vitamin D supplementation has significant effect on FBG [46].…”
Section: Discussionmentioning
confidence: 99%
“…Naghmeh Mirhosseini et al found that VD supplementation may significantly reduce FBG and HbA1c and facilitate glycemic control in type 2 diabetic patients [43]. However, Li et al didn’t find that VD supplementation would improve FBG or HbA1c [44]. Our meta-analysis assessed the effects of VD supplementation on glycemic control in DN patients, and showed that levels of FBG or HbA1c were not different between the experimental and the control group.…”
Section: Discussionmentioning
confidence: 77%
“…Other recent systemic analysis also suggested that large dosage, short-term vitamin D supplementation was most likely to yield preferred changes in vitamin D deficient, non-obese groups, Asians, especially Middle Easterners, and patients with optimal glycemic control at baseline (8) Even though Sri Lanka is a tropical country with sufficient sunlight throughout the year, vitamin D insufficiency is not uncommon among our population. But data on vitamin D status in Sri Lankans are very few.…”
mentioning
confidence: 73%